2007
DOI: 10.1007/s00787-007-0625-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of eating disorders

Abstract: ED that began at early ages in less severe forms and in females often persisted with increasing severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This is the first study that actually measured the eating attitudes of adolescent girls and did not rely solely on indices of BMI (e.g., Bolte et al 2000;Sobanski et al 1999). The two groups were matched for BMI that has been documented to affect eating attitudes (Lynch et al 2004;Sancho et al 2007) and, thus, the observed differences could be attributed mainly to the existence or absence of AS. Moreover, although this study is not longitudinal and there is no record of the eating habits of the participants during the first years of their life, it allows for the speculation that the eating problems that are evident among young children with autism (Hebebrand et al 1997;Keen 2007) seem to continue as they grow older and constitute a differentiating factor from their typically developing peers, as Asperger himself pointed out (1944).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study that actually measured the eating attitudes of adolescent girls and did not rely solely on indices of BMI (e.g., Bolte et al 2000;Sobanski et al 1999). The two groups were matched for BMI that has been documented to affect eating attitudes (Lynch et al 2004;Sancho et al 2007) and, thus, the observed differences could be attributed mainly to the existence or absence of AS. Moreover, although this study is not longitudinal and there is no record of the eating habits of the participants during the first years of their life, it allows for the speculation that the eating problems that are evident among young children with autism (Hebebrand et al 1997;Keen 2007) seem to continue as they grow older and constitute a differentiating factor from their typically developing peers, as Asperger himself pointed out (1944).…”
Section: Discussionmentioning
confidence: 99%
“…The girls whose age and BMI approximated more those of the target girls with AS were selected to participate in the study. So, the two groups were matched on chronological age and also on BMI (underweight, healthy, overweight), since the researcher wanted to ensure that any differences in their eating attitudes would not be influenced by their BMI as is documented in several studies (Lynch et al 2004;Mitchell et al 2005;Sancho et al 2007). The statistical analysis showed that there was no significant difference between the two groups either on age (t (110) = 1.91, p [ .05) or on BMI (t (110) = .11, p [ .05).…”
Section: Participantsmentioning
confidence: 99%
“…For example, disordered eating behaviors and body image concerns have been found to fluctuate among a non-clinical sample of adult college students followed over 20 years (Keel, Baxter, Heatherton, & Joiner, 2007). Yet only a few studies have investigated fluctuations in disordered eating behaviors and body disparagement during adolescence (Sancho, Arija, Asorey, & Canals, 2007;Stice, Marti, Shaw, & Jaconis, 2009), a time often identified as high risk for the onset of significant eating disturbances (Shisslak, Crago, & Estes, 1995;Stice et al, 2009). Investigating the stability (or instability) of eating and body image disturbances among youth serves to elucidate whether early detection and intervention efforts are necessary among younger populations in order to avoid or lessen the quality of life (Bamford & Sly, 2010) and financial (Crow et al, 2009) ramifications of eating disorders evident among adult populations.…”
mentioning
confidence: 99%
“…Findings from a two-year follow-up study of 200 Spanish boys and girls aged 9-13 indicate that while most youth do not engage in disordered eating, of those youth who did endorse eating disturbances, the most common diagnosis was eating disorder not otherwise specified (EDNOS; Sancho et al, 2007). Of the 21 boys and 25 girls who demonstrated disordered eating disturbances at Time 1, scores at Time 2 indicated that for some individuals (11 boys, 6 girls) symptoms had remitted.…”
mentioning
confidence: 99%
See 1 more Smart Citation